Fluvirucins B7–B10, new antifungal macrolactams from a marine-derived Nonomuraea sp. MYH522. Issue 24 (20th May 2022) - Yu, Hai; Chen, Shuo; Li, Hongji; Wang, Ruina; Jiang, Yuanying; Yan, Lan; Sun, Peng
Abstract : Four new 14-membered macrolactams, fluvirucins B7 –B10, were isolated from a marine rare actinomycete with known fluvirucin B6 . Some fluconazoles showed synergistic antifungal activity against fluconazole-resistant isolates of Candida albicans . Abstract : Marine rare actinomycetes are an important source of secondary metabolites. From a marine-derived actinomycete Nonomuraea sp. MYH522, four new macrolactams, fluvirucins B7 –B10, together with known fluvirucin B6 were isolated. Their structures were determined based on comprehensive analysis of HRESIMS and NMR spectroscopic data as well as by comparing 13 C NMR resonances and optical rotation values with those for related congeners. Fluvirucins are characterized by a 14-membered macrolactam attached by an aminosugar moiety. The discovery of fluvirucins B6 –B10 enriched the N -acetylated derivatives of fluvirucins. The diverse alkyl substituents at C-2 and C-6 implied substrate promiscuity in fluvirucin polyketide biosynthesis. These compounds didn't exhibit any antibacterial or antifungal activities when used alone, which suggested the importance of the free amino group in the antimicrobial activity of fluvirucins. However, fluvirucins B6, B9, and B10 showed synergistic antifungal activity with fluconazole against fluconazole-resistant isolates of Candida albicans .